Synthesis and characterisation of novel chiral smectic liquid crystalline elastomers containing menthol dimer-type side chain. Issue 12 (26th September 2018) - Jiang, Ying; Gao, Yiming; Lin, Zirui; Yan, Guiyang; Wang, Jiwei; Li, Jiusheng
ABSTRACT: A series of siloxane-based chiral smectic liquid crystalline elastomers (ChSLCEs) formed by a dimer-type smectic monomer (M1 ), a dimer-type chiral smectic monomer (M2 ) and a smectic cross-linker (CL) were reported. M1 and M2 were both new liquid crystals with dimer structures, and their chemical structures and purities were characterised by Fourier transform infrared spectra and 1 H NMR. The thermal stability and mesomorphism of monomers, cross-linker and ChSLCEs were examined by different analytical techniques. The results showed both monomers exhibited excellent smectic properties. The combination of different smectic phases from the two liquid crystalline side chains endowed the obtained ChSLCEs with good chiral smectic properties. The effect of different dosages of cross-linkers on the mesomorphic properties of the elastomers was also examined. The temperature ranges of mesophase-isotropic phases was narrowed with increasing addition of the cross-linkers according to the differential scanning calorimetry. All of the ChSLCEs exhibited good thermal stability from thermal gravity analysis results. The effective cross-link densities of ChSLCEs were calculated according to the swelling experiments to give the fact that the molecular weights between the cross-linking points decrease with the increase of the cross-linkers. Novel achiral smectic monomer (M1), chiral smectic monomer (M2), and an achiral smectic crosslinking agent (CL) have been synthesized to form a series of side chain chiral smectic liquid crystalline elastomers (ChSLCEs) LCE1-LCE7 by graft copolymerization with the poly(methylhydrogeno)siloxane backbone Graphical Abstract: